IN VIVO ANTI-DIABETIC ACTIVITY EVALUATION OF THE BARK OF CASCABELA THEVETIA L. IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Gogoi, Neelutpal; Bhuyan, Biman (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: In this study, the plant Cascabela thevetia L. was selected based on ethnomedicinal documentation reports for evaluation of the antidiabetic activity. The aim of this study was to carry out acute toxicity study and in vivo evaluation of antidiabetic activity in an animal model. Methods: Firstly direct extraction of the dried bark powder was done with methanol using soxhlet apparatus. After collecting the extract, acute toxicity study was performed according to OECD (Organization for Economic Cooperation and Development) guideline 425. For in vivo evaluation of antidiabetic activity, streptozotocin (STZ) and nicotinamide induced type 2 diabetic male rat model was used. Six groups containing six animals in each were taken for the in vivo study and marked as normal control, standard control, negative control and test controls. For all the animals body weight, body temperature, blood glucose levels were determined at an interval of 5 d. After 15 d of treatment different biochemical parameters like triglyceride, cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), alkaline phosphatase level (ALP), serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), total protein were determined and the results were evaluated by statistically using one-way analysis of variance (ANOVA). On the 15th day, all the animals were sacrificed and histopathological study of pancreases tissue was done. Results: The effects of the test extracts in lowering the blood glucose level and maintaining other biochemical parameters in the test groups were compared with the effect of standard drug metformin hydrochloride, 10 mg/kg body weight treated group and negative control group. The data were statistically evaluated using one-way analysis of variance (ANOVA) followed by Dunnet comparison all vs control method and taking significant at p<0.01. By comparing different biochemical parameters and histoarchitecture of the different test groups of animals, it was found that group V treated with 200 mg/kg body weight shows a significant effect. Conclusion: After performing the experiment it was found that the bark of Cascabela thevetia L. has the potential for blood glucose lowering activity and able to control abnormal lipids and enzymes level in blood. Further isolation of the compounds can lead to finding out the exact compound responsible for the activity. Â